The 6 C’s of Imaginative Play in Learning English to Develop Students’ Character - Telaumbanua, Yasminar Amaerita; Zebua, Elwin Piarawan; Telaumbanua, Nita Trima Niat; Mendrofa, Denista Riska Cahyani; Halawa, Mercy Dwiyul; Lase, Libertina; Mendrofa, Ester Jelita; Zai, Theresia Trines Anjelin; Harefa, Nurmawati; Zebua, Meniati; Gulo, Arniwati (Yayasan Pendidikan Bima Berilmu, 2025)
This community service examines the use of imaginative games in English learning to develop student character through the 6C framework: Collaboration, Communication, Content, Critical Thinking, Creative Innovation, and Self-Confidence. This activity was conducted with seventh grade students at Agios Nikolaus Gunungsitoli Christian Private Junior High School using observation sheets, field notes and student worksheets to analyze the impact of imaginative play on language learning outcomes and character building. The findings showed that most students demonstrated strong collaboration and communication skills, participating effectively in group activities and verbal interactions. Comprehension of materials and critical thinking skills also improved, with 87.5% of students (14 out of 16) showing a strong understanding of English learning materials, including grammar and vocabulary. A total of 68.75% of students (11 out of 16) were able to analyze and solve problems effectively, although further development is needed to improve their critical thinking skills. However, creative innovation was less developed, with only half of the participants actively exploring new ideas. Self-confidence saw a significant improvement, with 81.25% of students (13 out of 16) showing high levels of self-confidence. This reflects the effectiveness of the imaginative play method in helping students feel confident using language. In conclusion, the 6C’s imaginative play effectively supports language acquisition and character education, particularly in enhancing communication, collaboration, and confidence, though additional strategies are needed to further improve creativity and critical thinking. This approach offers a holistic and engaging method for integrating character development into English language learning.